(untitled) (Revista de História da UEG (REVHIST), 2023)
It analyzes the vestiges of northern participation in the Bull of creation of the bishopric of Piauí. The work of Parnaiba’s and neighbors to create a diocese in Piauí, based in Parnaíba – the northerners – has been neglected by historiography. However, the Bull of the diocese of Piauí (1901), based in Teresina, allows us to infer not only the importance, but also the determinant of this movement for its conception. Appropriating a hemerographic source – Northem newspaper – and documents, we sought to demonumentalize them (LE GOFF. 1990) and problematize their evidence (GINZBURG, 1989). Thus, comparing the Bull and the northern discourse, present in the newspaper of the same name, we found traces of this participation. The evidence of the silencing of northern action by the winning narrative, centralist, and the incongruities of the Bull testify to the historical process that triggered it, where different fronts disputed the protagonism for the creation of the bishopric of Piauí and your headquarters. Keywords: History. Bull. Diocese. Piauí. Parnaíba.